2015
DOI: 10.1093/jee/tov104
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of the Parasitoid Wasp Spalangia endius (Hymenoptera: Pteromalidae) and Insecticides against Musca domestica (Diptera: Muscidae) as Evaluated by a New Index

Abstract: Various insecticides for the control of the house fly Musca domestica L. were tested for compatibility with a biological control agent, the pupal parasitoid Spalangia endius Walker. Bioassays used the mode in which each organism was expected to be harmed by the insecticides, a surface contact bioassay for S. endius and a feeding bioassay for M. domestica. A Pesticide Compatibility Index (PCI) was created that allows comparison of LC50 values when the mode of exposure to a pesticide differs. First LC50 values w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…Imidacloprid, dinotefuran, and thiamethoxam were more toxic to the filth fly parasitoid Spalangia endius (Hymenoptera: Pteromalidae) than to the target pest (Musca domestica), thus making it unsuitable for controlling the flies (Burgess and King 2015). Also S. endius was attracted to imidacloprid granular baits and experienced more grooming activity, but not to those containing dinotefuran or other insecticides.…”
Section: Parasitoidsmentioning
confidence: 99%
“…Imidacloprid, dinotefuran, and thiamethoxam were more toxic to the filth fly parasitoid Spalangia endius (Hymenoptera: Pteromalidae) than to the target pest (Musca domestica), thus making it unsuitable for controlling the flies (Burgess and King 2015). Also S. endius was attracted to imidacloprid granular baits and experienced more grooming activity, but not to those containing dinotefuran or other insecticides.…”
Section: Parasitoidsmentioning
confidence: 99%
“…For example, thiamethoxam did not affect parasitoids, while imidacloprid reduced braconid, aphelinid and scelionid wasps. Burgess and King (2015) previously found that the LC 50 of imidacloprid was 4.5 times lower than that of thiamethoxam for a parasitoid of houseflies. Imidacloprid has a longer half-life and is an older chemical than thiamethoxam (Bonmatin et al, 2015; Simon-Delso et al, 2015), which could explain its greater non-target impacts.…”
Section: Discussionmentioning
confidence: 92%
“…Such exposure kills ~10% of females and no males. Parasitoids might encounter this concentration on a farm because 0.91535 μg/cm 2 of imidacloprid is the recommended application rate for imidacloprid when it is in house fly bait (Burgess and King 2015), and the pesticide disseminates and degrades over time (Rouchaud et al 1996, Burgess et al 2018.…”
Section: Parasitoid Exposure To Imidaclopridmentioning
confidence: 99%
“…In a Florida strain of S. endius, survival and subsequent ability to produce progeny and reduce fly numbers was reduced by contact with imidacloprid on a glass surface at concentrations well above recommended application rates (Burgess and King 2015). However, if females then had to move through manure-like media to locate hosts, parasitization ability was no longer affected (Burgess et al 2017).…”
mentioning
confidence: 99%